Neogene tectonic block rotations and margin curvature at the Pampean flat slab segment (28º-33º SL, Argentina) - Japas, M. S. (2012)
Available paleomagnetic data from the Pampean flat slab segment reveal a heterogeneous rotation pattern that is interpreted herein as the result of the overprinting of late NNW-WNW left-lateral brittle-ductile megashear zones that would be also responsible for the continental margin bending.